The Handbook of bilingual and multilingual education - Wright, Wayne E.; Boun, Sovicheth; García, Ofelia; Ohio Library and Information Network (Malden, MA : Wiley-Blackwell, 2015)
"Represents the first comprehensive reference work that covers bilingual, multilingual, and multicultural educational policies and practices around the world"--
Introduction: voice in multilingual research teamsCurrent debates in researching multilingualism; Researching multilingualism in multilingual teams; Analytic vignettes: introducing researcher and participant voices; Conclusion; References; 9 Intersections of Language Ideology, Power, and Identity; Introduction; Definitions of key terms and constructs; Bilingual education: psycholinguistic findings and principles; Bilingual education in the context of societal power relations; The polynesian context and the history of literacy in french polynesia
Includes bibliographical references and index
Keywords: Multilingualism -- Study and teaching -- Handbooks, manuals, etc; Education, Bilingual -- Handbooks, manuals, etc; Multicultural education -- Handbooks, manuals, etc; Electronic books; Handbooks and manuals; Handbooks and manuals